The Effect of Cassava Peel Powder on the Productivity of the Brown Oyster Mushroom (Pleurotus cystidiosus) - Rahmawati, Emmalia; Suparti, S (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2023)
The oyster mushroom cultivation medium is generally sengon sawdust. As time goes by, there is a buildup of agricultural waste, one of which is cassava skin. Cassava peel contains nutrients that are in accordance with the nutrients needed as a medium for oyster mushroom cultivation. The purpose of this study was to determine the effect of a mixture of sengon sawdust and cassava peels with different weight ratios on the productivity of the brown oyster mushroom (Pleurotus cytidiosus). The research design used was a completely randomized design with 7 treatments, including M0, M1, M2, M3, M4, M5, and M6. Then the data were analyzed with One Way Anova using SPSS 20. The results showed that the M2 treatment (90% sengon sawdust + 10% cassava peel powder) had the highest average wet weight, namely 84.9 g, and the fastest pinhead appearance time, which was 40.2 days after inoculation. Then in the M5 treatment (75% sengon sawdust + 25% cassava peel powder), the highest average number of fruit caps was 22.8 fruit caps. And the One Way Anova test shows that all three parameters have F count > F table. Thus, there is an effect of adding media mixed with sengon sawdust and cassava peels with different weight ratios on the productivity of brown oyster mushrooms.